The Effect of Training and Incentives on Work Productivity with Job Satisfaction as a Mediating Variable - Fatfa, Nadira Anasta; Safaria, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Analyzing effect of training on job satisfaction, incentives on job satisfaction, training on work productivity, incentives on work productivity, job satisfaction on work productivity, training on work productivity through job satisfaction, incentives on work productivity through job satisfaction. Quantitative research using PLS4 to measure Likert scale. Samples are 80 PT Bank DKI employees. The results of the findings Training has a significant effect on satisfaction, Incentives have an effect on satisfaction, training does not affect productivity, incentives do not affect productivity, satisfaction affects productivity, training affects productivity through satisfaction, incentives have a significant effect on productivity through satisfaction